Classroom-based language assessment literacy and professional development need between novice and experienced EFL teachers - Ima Fitriyah; Fitriatul Masitoh; Utami Widiati (Universitas Pendidikan Indonesia, 2022)
Classroom-based language assessment (CBLA) in the Indonesian context has become more significant since the shift of the assessment model from summative based assessment (Ujian Nasional or the final exam) to formative-based assessment (Asesmen Kompetensi Minimum (AKM); therefore, teachers need to develop their classroom-based language assessment literacy (CBLAL). The model places a greater emphasis on students' learning outcomes in class rather than final test scores. This study aims to examine the CBLAL level of experienced and novice EFL teachers, their perceptions of CBLAL, and their needs for CBLAL training. Quantitative and qualitative data were used in conjunction with a case study research design. The CBLAL questionnaire, adopted from Lan and Fan's work (2019), collected quantitative data from 55 EFL teachers. Meanwhile, the qualitative data were collected from four of them (novice and experienced) in the interview sessions. The CBLAL levels of 55 teachers are between functional and procedural-conceptual literacy levels. Both experienced (ETs) and novice teachers (NTs) could grasp fundamental principles in language assessment and can use them in the classroom. Although the ETs have higher levels, there is no significant difference in CBLAL levels between ETs and NTs. The study also revealed that the teachers' understandings of technical skills and language pedagogy were among the highest compared to their knowledge of theories and principles on language assessments. However, they indicated that still require professional development (PD) in CBLAL, despite their functional and procedural-conceptual literacy. The current study has pedagogical implications for both ETs and NTs. They should actively participate in various professional development activities, focusing on classroom evaluation.